The Universal Standard Encyclopedia: Volume 24: Ultraviolet- Washington - Joseph Laffan Morse 1902- (New York Standard Reference Works Publishing Company, Inc., 1956)
25 v. illus. (part col.) ports., maps (part col.)
Deluxe Edition . prepared under the editorial direction of Joseph Laffan Morse, editor in chief.
An abridgment of the New Funk & Wagnalls encyclopedia . The various volumes are frequently revised; this set contains the latest issue of each in the Library.
Keywords: Encyclopedias (3GdehShYGJs; General; Encyclopedias and dictionaries